First aid Q&A for the NBDE part II - Portnof, Jason E.; Leung, Timothy; Yeoh, Melvyn S. (New York McGraw-Hill Medical, 2010)
Machine generated contents note: Pharmacology -- Operative Dentistry and Prosthodontics -- Oral and Maxillofacial Surgery and Pain Control -- Orthodontics -- Pediatric Dentistry -- Endodontics -- Periodontics -- Radiology -- Pathology -- Patient Management, Public Health, Ethics and Biostatistics.
Includes index.
Keywords: Dentistry -- Examinations, questions, etc; Dentists -- Study guides -- Licenses -- Examinations -- United States; Emergencies -- Examination Questions; Emergency Treatment -- Examination Questions; Y học; Cấp cứu